2014
DOI: 10.1371/journal.pone.0088066
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Development of Peripheral Glial Cells in the Human Fetal Cochlea

Abstract: The adult human cochlea contains various types of peripheral glial cells that envelop or myelinate the three different domains of the spiral ganglion neurons: the central processes in the cochlear nerve, the cell bodies in the spiral ganglia, and the peripheral processes in the osseous spiral lamina. Little is known about the distribution, lineage separation and maturation of these peripheral glial cells in the human fetal cochlea. In the current study, we observed peripheral glial cells expressing SOX10, SOX9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 59 publications
(79 reference statements)
5
31
0
Order By: Relevance
“…Staining for p75NTR is present as early as GW 5 in the human fetal cochleo-vestibular ganglion (Vega et al 1999) and also among the peripheral processes of the human fetal cochlea at GW 9 (Locher et al 2014). In the present study, immuno-staining for this receptor was seen from GW 9 onwards and finally extended as far as the inner pillar cells at GW 12.…”
Section: Discussionsupporting
confidence: 61%
“…Staining for p75NTR is present as early as GW 5 in the human fetal cochleo-vestibular ganglion (Vega et al 1999) and also among the peripheral processes of the human fetal cochlea at GW 9 (Locher et al 2014). In the present study, immuno-staining for this receptor was seen from GW 9 onwards and finally extended as far as the inner pillar cells at GW 12.…”
Section: Discussionsupporting
confidence: 61%
“…3(A)]. Previously, we have shown that SOX10+ cells are present in the spiral ganglion and throughout the cochlear epithelium (Locher et al, 2014). In this study, we also detected SOX10 expression in the presumptive melanocytes bordering the stria vascularis [Fig.…”
Section: Resultsmentioning
confidence: 86%
“…3(B)]. We recently observed additional expression throughout the human fetal cochlear duct epithelium (Locher et al, 2013) and in all peripheral glial cells (Locher et al, 2014). Although it is likely that melanocytes play a major role in SNHL in WS or KS due to SOX10 mutations, it cannot be excluded that other SOX10+ cell types in the cochlea are involved as well.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is consistent with S100B location in a number of other nervous system locations. For instance, S100B was found associated with ensheathing cells of the rat olfactory pathway during development [41], peripheral glial cells of the human fetal cochlea [42], satellite cells of sensory, sympathetic and enteric ganglia, and in supporting cells of the adrenal medulla, myelinating and non-myelinating Schwann cells [31]. Peripheral neurons express both S100A1 and B, while the dorsal root ganglion contained S100B in the human peripheral nervous system.…”
Section: Distribution Of S100bmentioning
confidence: 99%